Preservation Effect of Gallnut Tannin on Fresh Macadamia Nuts - ZHANG Cheng, ZHANG Hong, SU Jianrong, TU Xinghao, XU Juan, LI Ying, LIU Lanxiang, TANG Xiaoning, MA Jinju (Shipin Kexue)
This study investigated the deoxidizing and moisture-absorbing properties of gallnut tannin and applied it to the preservation of fresh macadamia nuts under refrigeration and room temperature conditions. To evaluate its efficacy, this study measured the changes in the physicochemical indexes of macadamia nuts. The results showed that gallnut tannin possessed good deoxidizing and moisture-absorbing properties. Under refrigeration and room temperature conditions, it significantly reduced the oxygen content within the package, maintained the whiteness of macadamia kernel, delayed the darkening, preserved high levels of compressive hardness, puncture hardness and moisture content (> 5%), thus ensuring the taste of fresh macadamia kernel. In addition, the tannin significantly inhibited the increase in acid value, peroxide value, and aflatoxin B1 content. It could be concluded that gallnut tannin could inhibit lipid oxidation and rancidity and the growth of Aspergillus flavus in fresh macadamia nuts by reducing the oxygen content within the package, thus preserving the quality and taste and extending the shelf life. The results of this study provide new ideas to solve the problem of preserving fresh macadamia nuts, contributing to fill the gap in the fresh macadamia nut industry.